Media Animasi Powtoon dengan Model VAK (Visual Auditory Kinestetic) Pada Materi Fluida Statis untuk Meningkatkan Hasil Belajar Ditinjau dari Kemampuan Penalaran Induktif Siswa SMA Kelas XI - Farizi, Zakaria Al; Sulisworo, Dwi; Sahlan, Sahlan; Fitriani, Nadya; Abdullah, Abdullah (Universitas PGRI Semarang, 2022)
Physics is a very difficult subject to follow. This resulted in a decrease in student learning outcomes. Some of the background factors are 1) the different learning styles of students, and 2) the use of media that is not appropriate for the concept of physics, especially in a static fluid material. This research produces media in the form of animation from the powtoon application by applying the VAK learning model. The purpose of this study is to reveal the effectiveness of the media when compared with the use of conventional learning models on the same material. This study used the RD research method with a sample of one test class and one control class, each of which amounted to 20 students. This study also used a covariate variable in the form of students' inductive reasoning. From the results of this study, it can be revealed that the use of Powtoon animation media with the VAK model has a significant effect. This can be observed based on the results of the univariate test, and the Fcount value is greater than Ftable. Powtoon animation media is also effective for improving student learning outcomes. This is proven by the existence of testing and analysis of effect size as well as KKM. The two analyzes show that the effect size value is 0.88 which is included in the high category, and the minimum completeness criteria standard for students in the experimental class is 40% higher than the control class.